Periferia, Política e Cultura: O coletivo audiovisual Kinoférico do Bairro dos Pimentas - Matos, Fernanda Conceicao [UNIFESP] (2019)
This research, located in the field of urban anthropology, presents a reflection of the uses and meanings of the term periphery and collective term that appear as mobilizing elements of the actions of young residents of the region of Pimentas in the city of Guarulhos, to claim policies of rights and uses of the city, being the strategies, linked to art and culture, by them developed focus of this research that travels the paths of art-activism, politics and strengthening of artistic groups in the city. The ethnographic cutout turns to a collective in particular - the collective of audiovisual production Kinoférico.